PENGARUH TINGKAT KESEHATAN BANK DAN UKURAN BANK TERHADAP NILAI PERUSAHAAN - Maheswari, I Gusti Ayu Gita; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
The purpose of this study was to determine the effect of the bank with RGEC method and size of the company to the value of the company. The health of banks arranged by Bank Indonesia from 2012 was measured using the method RGEC (risk profile, good corporate governance, earnings, and capital). This study uses data on banking companies listed in Indonesia Stock Exchange 2012-2014. The use of the purposive sampling method with the number of samples taken by 22 companies from 40 populations banking companies that have gone pulbic. The data analysis technique used is multiple regression analysis. Based on the results of the study, it was found that the health of banks does not affect the value of the company, while the size of banks significant positive effect on the value of the company.
Keywords: the value of the company, the health of banks, RGEC, the size of the company